Panax ginseng and salvia miltiorrhiza supplementation abolishes eccentric exercise-induced vascular stiffening: a double-blind randomized control trial. Issue 1 (December 2016) - Lin, Hsin-Fu; Tung, Kang; Chou, Chun-Chung; Lin, Ching-Che; Lin, Jaung-Geng; Tanaka, Hirofumi
Abstract Background Muscle damage induced by unaccustomed or eccentric exercise results in delayed onset vascular stiffening. We tested the hypothesis that a 7-day supplementation ofpanax ginseng andsalvia miltiorrhiza prior to an acute eccentric exercise could attenuate arterial stiffening. Methods By using a double-blind study placebo-controlled randomized design, subjects were randomly assigned to either the Chinese herb (N  = 12) or the placebo group (N  = 11) and performed a downhill running (eccentric exercise) trial and a control (seated rest) trial. Results Muscle soreness increased 1–2 days after exercise similarly in both groups, whereas the herb group demonstrated a faster recovery on active range of motion. Plasma creatine kinase concentration increased significantly at 24 h in both groups but the magnitude of increase was attenuated in the herb group. Arterial stiffness as measured by carotid-femoral pulse wave velocity increased significantly at 24 h in the placebo group but such increase was absent in the herb group. Flow-mediated dilation did not change in either group. Plasma concentrations of CRP and IL-6 increased in the placebo group but no such increases were observed in the herb group. Changes in arterial stiffness induced by eccentric exercise were associated with the corresponding changes in IL-6 (r  = 0.46, P  < 0.05). Conclusions A short-term Chinese herb supplementation ofpanax ginseng andsalvia miltiorrhiza ameliorated the delayed onset vascular stiffening induced by acute downhill running exercise. Trial registration ClinicalTrials.gov: NCT02007304. Registered Dec. 5, 2013)